Parnassius loxias (Lepidoptera, Papilionidae) на территории СССР - Крейцберг, А.В.-А. (Вестник зоологии, 1984)
Parnassius loxias tashkorensis ssp. n. differs from the nominate subspecies by strong development of the black wing-pattern elements. Type locality: Kirghiz SSR, Kaindy (Kaindy-Katta) mountain range, Utsh-Tshat mountains, 70 km West of Pobedy Peak, Tashkoro village, 3100-3400 m. Type material: holotype ♂, paratypes 4 ♂, 5 ♀. The type locality of P. loxias loxias Püngeler, 1901 is restricted to the mountains North of Ak-su (Sinkiang, China). P. loxias rasitemensis Avinoff, 1916 suggested to be an infrasubspecific form.